2006
DOI: 10.1111/j.1574-6968.2006.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethambutol-induced alterations inMycobacterium bovisBCG imaged by atomic force microscopy

Abstract: Progress in understanding the structure-function relationships of the mycobacterial cell wall has been hampered by its complex architecture as well as by the lack of sensitive, high-resolution probing techniques. For the first time, we used atomic force microscopy (AFM) to image the surface topography of hydrated Mycobacterium bovis bacillus Calmette Guérin cells and to investigate the influence of the antimycobacterial drug ethambutol on the cell wall architecture. While untreated cells showed a very smooth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 18 publications
3
25
0
Order By: Relevance
“…2e). High-resolution images revealed a very smooth and homogeneous surface, consistent with previous work [28].…”
Section: Antimycobacterial Drugs Induce Major Ultrastructural Changessupporting
confidence: 90%
See 1 more Smart Citation
“…2e). High-resolution images revealed a very smooth and homogeneous surface, consistent with previous work [28].…”
Section: Antimycobacterial Drugs Induce Major Ultrastructural Changessupporting
confidence: 90%
“…Early investigations performed in air demonstrated the ability of AFM to visualize drug-induced alterations in the cell walls of Escherichia coli [7], Helicobacter pylori [8], and Staphylococcus aureus [6]. However, attempts to probe cell-drug interaction in situ, i.e., in relevant hydrated conditions, have been very limited so far [28].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these data demonstrate that it is possible to generate nanosystems to target intra-and extracellular mycobacteria, which could contribute to increase bacterial killing within granulomas at lower drug doses. Although we have not investigated the ultrastructure of mycobacteria treated with JVA-NP, it has been previously demonstrated that antibiotic treatment promotes changes in the bacterium (3,47). Moreover, physical and biochemical mechanisms by which JVA-NP interacts with M. tuberculosis merits further investigation.…”
Section: E-nmentioning
confidence: 99%
“…Non-destructive attachment may be achieved by immobilizing cells mechanically in a polymer membrane with pore size comparable to the dimensions of the cell (Kasas and Ikai, 1995). This method permitted the observation of bacterial cell surface dynamics, such as cell growth and division (Touhami et al, 2004), as well as structural changes resulting from cell wall-drug interactions (Verbelen et al, 2006).…”
Section: The Four Sessions Of the Conferencementioning
confidence: 99%